Capital imobiliário e a produção urbana de Fortaleza - estudo de caso para o período de 1950-1970 - Moreira, Francisco Giovani Pimentel (2004)
The objective of this work is to elaborate and to analyze the paper of the real estate capital, more precisely of the seller of urban lands, in the urbanization process happened in the Fortaleza city, among the decades of 1950 and 1970. For that reason, we chose José Gentil S/A Real estate, whose evidences presented along the study allows us to affirm that it was the most active company in the market of urban lands of Fortaleza, in the considered period, be for the volume of businesses or be for the symbolic power that it contains in itself. We showed a theme- the performance of the Real estate, inserted in movements that concern the growth social- economic of the city, to the exercise in the several ways of power and construction of nets that they create and reproduze the dominance relationships in the extent of a social process of such magnitude , marked by practices (clientelistas, personalistas) and centralizing that they have been giving the tonic of the political and social process in Fortaleza. Finally, founded in the instrumental theoretical that guides us, we showed in an empiric way how the succession of social- economic facts went weaving a favorable scenery the performance of a linked social group to the real estate (fundiário) section, that, owners the economical capital and social prestige, acted with opportunity sense aiming at, before any other thing the wealth accumulation and power, pillars of support of the groups and local dominant classes.